The Latent Domains of Religious Moderation Attitudes and Intercultural Competencies Within the Contexts of Multireligious and Multicultural Societies - Shonhaji (Journal of Population and Social Studies [JPSS], 2025)
Religious moderation attitudes (RMAs) and intercultural competencies (ICs) are two crucial elements that must be internalized within Indonesia’s multireligious and multicultural societies. This study aimed to investigate the latent domains of RMAs and ICs and the cultivation of such latent domains to facilitate RMAs and ICs’ internalization. This phenomenological study purposively recruited 224 multireligious and multicultural people living in 8 regions of Indonesia. These regions became the loci due to recommendations of prior studies. Data on RMAs and ICs’ latent domains were collected through interviews and observations, and those of the cultivation of the foregoing latent domains were obtained from focus group discussion (FGD). The data analyzed using an interactive model revealed that RMAs had eight latent domains, which subsumed respect for religious freedom, openness to belief differences, awareness of pluralism, promoting harmony, active community participation, understanding extremism, cooperative religious leadership, and commitment to peace. The data then revealed latent domains of eight ICs: inclusive education, cross-cultural collaboration, reflective education, social criticism, empathy, cultural sensitivity, effective communication skills, and understanding diversity benefits. The data also showcased many strategies used by various societal parties to cultivate RMAs and ICs’ latent domains effectively. These parties were religious leaders, community leaders, social and cultural institutions, society members, educational institutions, local government, and media. It is recommended that further studies be carried out to psychometrically work on these latent domains.